DETERMINAN KEPUASAN NASABAH DALAM MEMBENTUK LOYALITAS NASABAH PT BTN CABANG AMBON - Tjokro, Cynthia Imelda (Jurnal Minds: Manajemen Ide dan Inspirasi, 2018)
This study wanted to know the factors that are determinant of satisfaction in order to form customer loyalty PT BTN Ambon Branch. The purpose of this research is to analyze the influence of service quality factor, trust, customer value, product superiority, corporate image to satisfaction and customer loyalty of PT BTN Ambon Branch. This research was conducted at PT. BTN Ambon Branch. Data analysis using path analysis to know the influence of independent variable to dependent variable, either directly or indirectly. The results of this study indicate that service quality (X1), trust (X2), customer value (X3), Product Superiority (X4), and Corporate Image (X5) affect satisfaction (Y1) and customer loyalty (Y2), either directly or indirectly directly.